Novel reversible data hiding based on difference expansion - Jian-gao LUO; Guo-qiang HAN; Yan WO (Tongxin xuebao)
A novel reversible data hiding algorithm based on difference expansion called ACD was proposed, which used the so-called adaptive change direction technology. ACD embeds data by expanding the differences of neighboring pixel values. In a pair of pixels, a pixel was for reference and the other was for transform. ACD first estimates the type of the pixels area, then chooses transform pixels by the type that it chooses the large value pixel in dark areas and the small value pixel in bright areas, or else selects the pixels by default direction. Theoretical analysis and experimental results show that ACD solves the problem of gray overflow increased dramatically in the reversible data hiding based on prediction error expansion (PEE)when the carrier is very dark or bright. Compared with the PEE with the existing gray overflow solution, ACD is suitable for wider types of carrier and has more stable performance.